2014
DOI: 10.1055/s-0034-1397332
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Voice Self-Assessment with Auditory Perceptual Analysis in Patients with Multiple Sclerosis

Abstract: Introduction Disordered voice quality could be a symptom of multiple sclerosis (MS). The impact of MS on voice-related quality of life is still controversial. Objectives The aim of this study was to compare the results of voice self-assessment with the results of expert perceptual assessment in patients with MS. Methods The research included 38 patients with relapse-remitting MS (23 women and 15 men; ages 21 to 83, mean = 44). All participants filled out a Voice Handicap Index (VHI), and their voice sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…32 This condition may lead to diet restrictions (bolus consistency or volume), associated risks (e.g., bronchoaspiration), and exclusive use of alternative feeding routes. 33 Our study showed significantly lower SWAL-QOL scores (for individual items-burden, eating desire, duration, symptom frequency, food selection, communication, mental health, and fear-and total score) in the CG at the 3-month assessment. When eating is considered a burden, it may reflect a patient's fear of immobility or muscle fatigue.…”
Section: Discussionsupporting
confidence: 43%
“…32 This condition may lead to diet restrictions (bolus consistency or volume), associated risks (e.g., bronchoaspiration), and exclusive use of alternative feeding routes. 33 Our study showed significantly lower SWAL-QOL scores (for individual items-burden, eating desire, duration, symptom frequency, food selection, communication, mental health, and fear-and total score) in the CG at the 3-month assessment. When eating is considered a burden, it may reflect a patient's fear of immobility or muscle fatigue.…”
Section: Discussionsupporting
confidence: 43%
“…Comparing the results obtained in this study with other studies, it can be noticed that in all studies the mean values of VHI are relatively low, indicating only a slight degree of self-reported voice disorder. The results are for instance: 15.64 and 16.68 in studies conducted by Bauer et al (n=36 and n=38 respectively), (Bauer et al, 2013, Bauer et al, 2015 and 5.92 in a study by Hamdan et al (n=59) (Hamdan et al, 2012). The higher value obtained in our study, indicating worse voice quality reported by the patients may result from the fact that the study was conducted on a much bigger group of patients (n=107) with a formal neurological MS diagnosis.…”
Section: Discussionsupporting
confidence: 39%
“…The correlation between V-RQOL and D ( Table 3 ) clearly provides evidence of the impact of dysphonia on patient quality of life 25 , 26 , 27 , even when these scores were not especially high. The impact of dysphonia on different populations should also be considered.…”
Section: Discussionmentioning
confidence: 94%